ORGANIZATION OF EDUCATIONAL WORK ON THE FORMATION OF VALUABLE ATTITUDE TO OWN HEALTH OF CHILDREN AGED 6-7 YEARS OF LIFE IN INTERACTION OF PRE-SCHOOL EDUCATION INSTITUTION AND PRIMARY SCHOOL - PYECHKA , LARYSA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article highlights the results of the approbation of the method of forming the basis of valuable attitude to the health of children aged 6-7 years of life in the interaction of the institutions of preschool education and primary school. The stages of organization of experimental work are presented in the paper. The basic forms and methods of formation of the basis of valuable attitude to the own health of children 6-7 years of life are determined. The achievements of pre-school childhood with the purpose of their enrichment at the junior school age and ensuring the consistent growth of the child's personality are determined. The necessity of taking into account the principle of continuity in the work of the institution of preschool education and primary school is proved in relation to the formation of healthy lifestyle habits of children. The work with teachers, parents is analyzed in the context of the problem under investigation.